2012
DOI: 10.1016/j.pscychresns.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Impaired functional but preserved structural connectivity in limbic white matter tracts in youth with conduct disorder or oppositional defiant disorder plus psychopathic traits

Abstract: Youths with conduct disorder or oppositional defiant disorder and psychopathic traits (CD/ODD+PT) are at high risk of adult anti-social behaviour and psychopathy. Neuroimaging studies demonstrate functional abnormalities in orbitofrontal cortex and the amygdala in both youths and adults with psychopathic traits. Diffusion tensor imaging in psychopathic adults demonstrates disrupted structural connectivity between these regions (uncinate fasiculus). The current study examined whether functional neural abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 49 publications
4
90
2
2
Order By: Relevance
“…Given the possible neurodevelopmental aspect of interhemispheric connectivity deficits in individuals with psychopathy, 9 research in children or adolescents with psychopathic traits may provide more conclusive evidence. In line with this, Finger and colleagues 47 have shown that adolescents with conduct disorder or oppositional defiant disorder combined with psychopathic (i.e, callous-unemotional) traits have intact microstructural integrity of white matter tracts. However, deficits in functional connectivity are already present in these youths.…”
Section: Discussionmentioning
confidence: 75%
“…Given the possible neurodevelopmental aspect of interhemispheric connectivity deficits in individuals with psychopathy, 9 research in children or adolescents with psychopathic traits may provide more conclusive evidence. In line with this, Finger and colleagues 47 have shown that adolescents with conduct disorder or oppositional defiant disorder combined with psychopathic (i.e, callous-unemotional) traits have intact microstructural integrity of white matter tracts. However, deficits in functional connectivity are already present in these youths.…”
Section: Discussionmentioning
confidence: 75%
“…Within these theories, the amygdala is generally hyporesponsive to negative affective stimuli and lacks optimal functional interactions with paralimbic neurocircuits, leading to deficient affective reactivity (particularly to fear), biased attention modulation, and poor associative learning [Anderson and Kiehl, 2012; Blair, 2013a; Blair, 2015]. Very few studies, though, have actually investigated amygdala functional networks in relation to psychopathy, yielding conflicting results of both enhanced and diminished network integrity [Aghajani et al, 2016; Contreras‐Rodriguez et al, 2015; Decety et al, 2013a; Finger et al, 2012; Marsh et al, 2011; Motzkin et al, 2011; Yoder et al, 2015]. Most of these studies additionally examined psychopathy as a categorical or unidimensional construct, overlooking its behaviorally and neuronally separable trait assemblies [Carre et al, 2013; Cohn et al, 2014, 2015; Philippi et al, 2015; Sadeh and Verona, 2008; Seara‐Cardoso and Viding, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Another imaging study showed that youths with CD or ODD and high levels of psychopathic traits showed disruptions in amygdala-prefrontal functional connectivity [78]. The same research group reported that youths with both conduct problems (aged 10-17 years) and elevated CU traits demonstrated increased activity bilaterally in the medial frontal gyri and abnormal activity within the ventromedial prefrontal cortex during punished reversal errors compared to normal controls.…”
Section: Neurobiological Factorsmentioning
confidence: 94%